The effect of hydrodynamic insole on foot kinematics in individuals with flexible flatfoot: Case series using a single-subject design. (April 2019) - Barati, Kourosh; Saeedi, Hassan; Hajiaghaei, Behnam; Jalali, Maryam; Curran, Sarah
The medial longitudinal arch of the foot is a dynamic structure while walking. The mobility of this structure in people with flexible flatfoot is partially or completely absent. The aim of this study was to investigate the efficacy of an insole that was designed to retrieve the medial longitudinal arch mobility in people with flatfoot. The study was a case series using a single-subject design. This single-subject design study was based on three subjects with flexible flatfoot. This study was designed in two phases: the baseline phase and the intervention phase. Each phase included five measurement sessions that were done in 5 consecutive weeks. We used the celeration-line method to detect the significant differences between the phases. Significant differences were recorded in the walking velocity, step length, and medial longitudinal arch mobility parameters when using the hydrodynamic insole. The results of this study showed that using the hydrodynamic insole may have a positive effect on the foot kinematics and gait parameters in people with flexible flatfoot.